Oil and protein compositions of a groundnut (Arachis hypogaea l.) mutant matjan gamma 20 - Cheah, C. H.; Tan, N. H.; Khor, H. T. (1990)
The oil and protein compositions of a groundnut (Arachis hypogeae l.) mutant matjan gamma 20 induced by gamma radiation as well as the parent and three other genotypes were investigated. The mutant expressed several important improvements, over it parent including an increase in the oleic:linoleic ratio without increasing the behenic acid content, an increase on oil yield per kernel and an increase in tryptophan content without any decrease in protein content.